THE IMPOTANCE OF HEALTY PSYCHOLOGY, EXERCISE IN DAILY LIFE FOR A HEALTY AND FIT BODY - Hamdani, Ainin; Hardovi, Bahtiar Hari; Aprilianto, Rizky (Gladi : Jurnal Ilmu Keolahragaan, 2025)
Regular exercise has been proven to be effective in maintaining physical and mental fitness, but there are still many people, including farmers in Pondokrejo Village, who ignore it because they are busy and believe that farming activities are enough to replace exercise. Lack of understanding and limited facilities contribute to low interest in regular exercise, which risks reducing long-term fitness. This research aims to describe the interests and habits of the people of Pondokrejo Village, Tempurejo District, Jember Regency, towards sports activities. Using a descriptive quantitative approach, data was collected through an online questionnaire from 100 respondents aged 18–59 years. The research results show that the majority of respondents have good and regular exercise habits, with a frequency of 3-5 times a week, and are accompanied by an understanding of the importance of warming up and cooling down. These findings indicate that respondents not only live an active lifestyle, but also realize the physical and psychological benefits of exercise. However, there are still some people who pay little attention to sports because of busy work activities, especially among farmers. Therefore, ongoing education is needed regarding the importance of exercise as part of a healthy lifestyle and long-term disease prevention.